Namowa lub pomoc w samobójstwie – aspekty prawnokarne, porównawcze i kryminalistyczne - Gawliński, Andrzej; Zero, Daniel (Studia Prawnoustrojowe, 2021)
Each year in Poland there are over 5,000 deaths as a result of suicide. Even more suicide attempts have been reported. Although suicide is not subject to criminal sanction, it is penalized to cause a person to take his own life through abetting or aiding (Article 151 of the Penal Code), physical or mental abuse (Article 207 § 3; Article 352 § 3) and stalking or impersonation (Article 190a § 3). From the point of view of investigative practice, detecting these cases and collecting evidence is problematic. The aim of the article is a criminal law analysis of the crime under Art. 151 of the Penal Code along with a reference to similar provisions in selected countries and discussion of forensic aspects. In Poland the number of instituted proceedings and established crimes, as well as convictions under Art. 151 of the Penal Code concerning the total number of suicides, is small. Due to detection and evidence problems, it is difficult to estimate the actual scale of the crime under Art. 151 of the Penal Code. Due to the significant and very dynamic development of the network, a possible amendment to Art. 151 of the Penal Code, covering new forms of persuasion or assistance in suicide – via the Internet.